The Curative Effect of Berberine Nanoparticles and Cisplatin Combination Therapies Against Hepatocarcinogenesis-Induced By N-Nitroso-Diethylamine In Male Rat - Mohamed, Nema Abdelhameed; Ali, Awatef Mohamed; Ghareeb, Doaa Ahmed; Mohamed, Adham Rashed; Elmokhtar, Yasmin Mohamed (JOURNAL OF ADVANCES IN BIOLOGY, 2018)
This study aimed to investigate whether berberine nanoparticles (BBR-NPs) and/or cisplatin supplementation could prevent hepatocarcinogenesis-induced by N-nitroso-diethylamine (DENA) in male rats. Male Wistar albino rats were divided into five groups; Group 1: Control; Group 2: DENA-CCl4; Group 3: DENA-CCl4+Cisplatin; Group 4: DENA-CCl4+BBR-NPs; Group 5: DENA-CCl4+Cisplatin+BBR-NPs. DENA-CCl4 significantly increase AST, ALT, ALP, LDH, GGT, AFP activities and total bilirubin, while, 5, NT, total protein and albumin decreased. DENA-CCl4 treatment caused increment in MDA levels and reduction in SOD, CAT, GPx and GSH in liver tissues. Moreover, DENA-CCl4 increase the gene expression of ADAM17 and TNF-a however, P53 was declined. In addition, DENA-CCl4 caused severe histopathological lesions in the liver tissue. Interestingly, administration of berberine nanoparticles alone or in combination with cisplatin improves the hepatocarcinogenesis induced by DENA-CCl4 on the physiological, biochemical, molecular and histological levels by decreasing oxidative stress and preserving gene expression of ADAM17, TNF-I and P53. The present findings suggest that BBR-NPs with cisplatin might offer a promising strategy for the prevention of liver cancer.